Corrosive effect on saturated pool boiling heat transfer characteristics of metallic surfaces with hierarchical micro/nano structures - Wei Xu; Longchang Tang; Ningkang Zhao; Kun Ouyang; Xiaoqiang He; Xiaojing Liu (Heliyon, 2024)
Surface modification is of critical interest to enhance boiling heat transfer in terms of heat transfer coefficient or critical heat flux (CHF), which is significantly affected by distinct surface morphology and wettability and it can improve the efficiency and safety of equipment. Furthermore, actual service environment may cause severe corrosion to the processed structured surfaces while its consequence on boiling heat transfer is still obscure. In this article, comprehensive researches are conducted to unravel corrosive effect on metallic samples made of stainless steel (SS) and Inconel materials with microstructures. Different constructions (i.e., microgroove, microcavity and micropillar array) and characteristic dimensions (∼20, 50 μm) of microstructure, various duration time (up to 300 days) and pH values (∼7.0–8.5) of corrosive environment are compared thoroughly. Conclusions can be drawn that not all microstructures can enhance pool boiling heat transfer characteristics, especially in terms of CHF values. More importantly, CHF value of SS microgroove sample firstly increases from 60.94 to 94.09 W·cm−2 in 50 days, then decreases to 47.77 W·cm−2 in 300 days, which can be attributed to competition result between formation of hierarchical micro/nano structure with enhancing wicking capability and chemistry condition with increasing contact angle. In addition, distinct bubble dynamics during pool boiling is also analyzed. The insights obtained from this article can be used to guide surface modification method and to reveal evolvement rule of engineered metallic surface in highly corrosive and harsh boiling heating transfer environment.